2017
DOI: 10.1016/j.neurobiolaging.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic or pharmacological activation of the Drosophila PGC-1α ortholog spargel rescues the disease phenotypes of genetic models of Parkinson's disease

Abstract: Despite intensive research, the etiology of Parkinson's disease (PD) remains poorly understood and the disease remains incurable. However, compelling evidence gathered over decades of research strongly support a role for mitochondrial dysfunction in PD pathogenesis. Related to this, PGC-1α, a key regulator of mitochondrial biogenesis, has recently been proposed to be an attractive target for intervention in PD. Here, we showed that silencing of expression of the Drosophila PGC-1α ortholog spargel results in PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…Statistical significance: ### p < 0.001 versus control parental flies; ***p < 0.001 versus Q128HD-FL without meldonium supplementation; one-way analysis of variance with post-hoc Bonferroni's test. Bars represent the means ± SD; n = 3 [Color figure can be viewed at wileyonlinelibrary.com](Ng et al, 2017). In contrast, Spargel overexpression significantly improved the climbing performance of parkin null flies, a strain of Drosophila characterized by disability in mobility.…”
mentioning
confidence: 99%
“…Statistical significance: ### p < 0.001 versus control parental flies; ***p < 0.001 versus Q128HD-FL without meldonium supplementation; one-way analysis of variance with post-hoc Bonferroni's test. Bars represent the means ± SD; n = 3 [Color figure can be viewed at wileyonlinelibrary.com](Ng et al, 2017). In contrast, Spargel overexpression significantly improved the climbing performance of parkin null flies, a strain of Drosophila characterized by disability in mobility.…”
mentioning
confidence: 99%
“…Staats et al (2018) and Wagner et al (2015) observed an upregulation of srl in flies treated with drugs that promote increased lifespan and locomotor performance in males, but such correlative studies do not address its mechanism of action. srl knockdown in muscle did produced morphological abnormalities in mitochondria, whilst its overexpression in dopamine neurons compensated for the effects of parkin deficiency (Ng et al, 2017). However, these findings relied on a single (unspecified) RNAi line and on the same overexpression strain used in our study, and did not document effects on mitochondrial gene expression or activity.…”
Section: A Different Role For Spargelmentioning
confidence: 67%
“…Our results suggest that disruption of the AMPK pathway may precipitate PD whereas augmenting AMPK activity may mitigate the disease. Supporting this, we have demonstrated that AMPK activation ameliorates the disease phenotypes in Drosophila genetic Short Report 4 models of PD (5), and in a manner that is dependent on its downstream target peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), a regulator of mitochondrial biogenesis (6). We further shown that pharmacological administration of AMPK activators restores the levels of midbrain pAMPK and PGC-1α expression in Parkin-deficient mice (4).…”
Section: Introductionmentioning
confidence: 63%
“…To better understand the molecular underpinnings of our observations, we examined for any changes in terms of mitochondrial homeostasis, considering that the protective effects of AMPK in ameliorating PD-related phenotypes is mediated by its downstream effector and mitochondrial biogenesis regulator PGC-1a (6). From the representative confocal images, there are fewer mitochondria (reduction in TOM20 staining) in the TH-expressing nigral DA neurons of AMPK-cKO mice compared to AMPK-WT mice (Fig.…”
Section: Ampk-cko Mice Display Aberrations In Mitochondrial Homeostasismentioning
confidence: 99%